Qualitative exploration of infant and young child feeding practices in rural field practice area of SSIMS and RC: a focus group discussion study - R. G., Geethalakshmi; J. S., Smitha Yadav (International Journal Of Community Medicine And Public Health, 2017)
Background: The art of infant feeding is a blend of biology and culture. A large no of women in India are already traditionally inclined towards infant and young child feeding (IYCF) practices. The need is to identify specific problems in local community. The strong influence of socio-cultural milieu is detrimental to health of the child. It is important that every opportunity of contact of health personnel with care givers should be taken to counsel on infant feeding. Methods: A Focus group discussion Study was conducted between February and May 2017. Mothers with child less than 2 years of age, grand-mothers and health care providers (ASHA’s and ANM’s) who form the stake holders population of IYCF were involved after taking consent. Each Homogenous group had 6-12 participants. Qualitative information was collected till saturation was achieved. Results: 6 FGD’s in each homogenous group were conducted. Colostrum was considered impure, giving honey as pre lacteal feed was a ritual, inadequate milk secretion, lack of knowledge about when and what complementary feeds to be given and also about importance of breast feeding till 2 years of age and giving artificial feeds. These were reasons for improper IYCF practices. Conclusions: This study emphasises the importance of group opinion prevailing in the local community for IYCF practices which is essential for instituting health education.